The Effect of Cast Films of Bovine Mucin and Prosopis Gum Containing a CicatrinÂ® Powder on Wound Healing - Momoh, MA; Adikwu, MU; Eraga, SO (Dhaka University Journal of Pharmaceutical Sciences, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Orodispersible tablets of carbamazepine were prepared with a view to enhance patient compliance by direct compression method using 3Â² full factorial design. Crospovidone (2-10% w/w) was used as superdisintegrant and microcrystallinecellulose (0-30% w/w) was used as diluent, along with directly compressible mannitol to enhance mouth feel. The tablets were evaluated for hardness, friability, thickness, drug content uniformity, in vitro dispersion time, wetting time and water absorption ratio. Based on in vitro dispersion time (approximately 10 s); the formulation containing 2% w/w crospovidone and 30%w/w microcrystallinecellulose was found to be promising and tested for in vitro drug release pattern (in pH 6.8 phosphate buffer), short-term stability (at 40Âº/75 % RH for 3 w) and drug-excipient interaction. This formulation showed four-fold faster drug release (t25%) compared to the conventional commercial tablet formulation. Short-term stability studies on the formulation indicated that there are no significant changes in drug content and in vitro dispersion time (p < 0.05). Â Key words: mucin, Prosopis gum, cicatrin, healing DOI = 10.3329/dujps.v7i1.1200 Dhaka Univ. J. Pharm. Sci. 7(1): 7-10, 2008 (June)